2014
DOI: 10.1128/jcm.02453-13
|View full text |Cite
|
Sign up to set email alerts
|

Global Improvement in Genotyping of Human Papillomavirus DNA: the 2011 HPV LabNet International Proficiency Study

Abstract: Cervical cancer is the third most common cancer among women worldwide, with an estimated 530,000 new cases diagnosed annually. Human papillomavirus (HPV) infection is linked to Ͼ99% of cervical cancers (1). The most important highrisk types (HPV16 and HPV18) account for about 70% of all invasive cervical cancers worldwide (2).The introduction of HPV vaccines has highlighted the need for accurate and internationally comparable HPV DNA detection and genotyping methodologies. This is an essential component in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 35 publications
(39 reference statements)
1
63
0
3
Order By: Relevance
“…Successive proficiency studies have demonstrated improved proficiency among participating laboratories over time [33,34].…”
Section: Laboratories Identifying Correctly 50 International Units (Imentioning
confidence: 98%
“…Successive proficiency studies have demonstrated improved proficiency among participating laboratories over time [33,34].…”
Section: Laboratories Identifying Correctly 50 International Units (Imentioning
confidence: 98%
“…The WHO proficiency panel is designed for evaluating HPV assays used in HPV vaccine research and HPV surveillance (Eklund et al, 2014). Samples contained single or multiple HPV genotypes (6, 11, 16, 18, 31, 33, 35, 39, 45, 51, 52, 56, 58, 59, 66, 68a and 68b), at concentrations of 5 to 500 International Units (IU) or genome equivalents (GE) per 5 μL of DNA (Marcuccilli et al, 2015).…”
Section: Who Hpv Labnet Proficiency Studymentioning
confidence: 99%
“…These very sensitive assays are capable of identifying up to 37 individual genotypes including all vaccine-targeted types, the remaining high-risk genotypes and additional low-risk genotypes. A drawback of full-genotyping assays that use consensus primer sets such as PGMY and GP5+/6+ is the tendency for HPV 16 and several other types to outcompete the amplification of a subset of genotypes that are less efficiently amplified by PCR, which theoretically has the potential to artificially alter genotype prevalence estimates between pre-vaccinated and post-vaccinated populations [56][57][58]. This can be overcome by using assays that rely on type-specific primer sets [58]; currently these assays generally identify a smaller range of genotypes and are often more labour-intensive, but recently developed assays may overcome these drawbacks.…”
Section: Hpv Assaysmentioning
confidence: 99%